Karavannoe: Mineralogy, trace element geochemistry, and origin of Eagle Station group pallasites. (20th April 2022) - Teplyakova, Svetlana N.; Lorenz, Cyril A.; Ivanova, Marina A.; Humayun, Munir; Kononkova, Nataliya N.; Borisovsky, Sergey E.; Korochantsev, Alexander V.; Franchi, Ian A.; Zinovieva, Nina G.
ABSTRACT: Karavannoe is a pallasite found in Russia in 2010. The mineralogy, chemistry, and oxygen isotopic composition indicate that Karavannoe is a member of the Eagle Station Pallasite (ESP) group. Karavannoe contains mostly olivine and subdued interstitial Fe, Ni‐metal. Zoned distribution of FeO in small, rounded grains of olivine and FeO and Al2 O3 in chromite shows that the cooling rate of the melt was fast during the crystallization of the round olivine grains. Siderophile element distribution and correlations of Au‐As and Os‐Ir concentrations in Karavannoe and the other ESP metal record its magmatic origin. FeO‐rich composition of olivine, low W and Ga, and high Ni abundances in the Karavannoe metal indicate the formation of the metal from an oxidized chondrite precursor. Model calculations demonstrate that the ESPs' metal compositions correspond to the solids of the fractional crystallization of CV‐ or CO‐chondrite‐derived metallic liquids. The Karavannoe metal composition corresponds to the solid fraction crystallized after 40% fractional crystallization. The Mg/(Mg+Fe) atom ratio of complementary silicate liquid corresponds to Fo70, possibly indicating that the olivine is not in equilibrium with the metal and could have been a product of the late evolutionary processes in the Karavannoe parent body mantle. In any ESP genesis Karavannoe was not in equilibrium with its metal and is a product of mantle differentiation processes. Olivine of Karavannoe and ESPs is similar in composition, while the metal is different. We propose a model of ESP formation involving an impact‐induced intrusion of liquid core metal into a basal mantle layer, followed by fractional crystallization of the metal. The metal textures and chemical zoning of Karavannoe minerals point to remelting and rapid cooling due to a later impact event.